KEPASTIAN HUKUM GADAI TANAH DALAM HUKUM ISLAM (TELAAH HUKUM GADAI ISLAM TERHADAP PELAKSANAAN GADAI TANAH DI KABUPATEN BOGOR) - Muhammad Sulaeman Jajuli (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2017)
Fiduciary   is  a  usual  universal  sociological  phenomenon  that  occur  everywhereespecially in our country. In Indonesia society, it grows conventionally and based on habit that have occurred for generation to generation. Land fiduciary in Bogor district has done for long time. Practice  of land fiduciary that occurred was running without any document for legal certainty guarantee.  Meanwhile, academically legal certainty guarantee  is a theory that has not been developed yet by Islamic law jurist. Based on research  results, concluded that 1. Implementation of rule according  to Islamic law fiduciary land must meet the requirements and harmonious elements of fiduciary. Terms pledge the land is; can be handed over, useful, or fixed assets can be moved, not mixed up with someone else's property, and land is fiduciary owned by râhin.  The pillars pledge is âqid (presence of râhin and murtahin), al-ma'qûd (marhun), al-ma'qûd 'alaih (marhûnbih) and shîghat. Practice fiduciary land in legal term in Islam is called bay al- wafa' not rahn because the terms and pillars contained in rahn accordance  with the rules  in  bay al-wafa.  2.  The definition of legal  certainty  in  the  implementation of fiduciary land under Islamic law is evidence in the form of written documents in the form of stamp duty, or paper sealed and the presence of witnesses from both parties’ murtâhin  and  râhin.  For  the  Bogor  regency  society,legal  certainty  is  considered sufficient to the existence of an element of trust between two sides (murtahin and râhin) without the use of evidence or documents and witnesses. 3. Based to the study of the law of Islamic fiduciary land, practices of fiduciary land in Bogor regency society belong to the category imperfect contract.  Said to be imperfect because of the implementation agreement contained elements of usury which is forbidden by the religion that is taking advantage  of more than  possession lent. Besides the practice  of fiduciary in Bogor regency become less perfectly even invalid because it is contrary to the commands of Allah in the ◌Al-Qur'an about the principle of 'faktubuh' (Surah al-Baqarah/2:282) Key Word: Kepastian Hukum, Hukum Islam, Gadai Tanah, Bogor